Color Directional Binary Code for Image Indexing and Retrieval - Bonde, M. V; Doye, D.D (International Journal of Computer Sciences and Engineering, 2025)
This research paper proposes a novel algorithm meant for image indexing and retrieval, by integrating color and texture features. First, the RGB image is converted to HSV space, then these space features are collected by constructing H & S space histograms and texture features, which are collected from V space of an image by Directional Binary Code (DBC). In the proposed algorithm both, color histograms and texture feature, are then concatenated to generate the feature vector. Using feature vector of query image, similar images are then extracted using different distance measures. The retrieval results for this proposed algorithm is tested over Corel 1000 image database. After investigation, results demonstrate the substantial improvement in terms of retrieval precision and recall as equated to LBP, DBC feature algorithms